2019
DOI: 10.3389/fgene.2019.00525
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-Catenin/LEF1 Pathway Promotes Cell Proliferation at Least in Part Through Direct Upregulation of miR-17-92 Cluster

Abstract: The miR-17-92 cluster is involved in animal development and homeostasis, and its dysregulation leads to human diseases such as cancer. In the present study, we investigated the functional link between miR-17-92 cluster and Wnt/β-catenin signaling pathway in ICP2 and DF1 cells. We demonstrated that ectopic expression of either LEF1 or β-catenin increased the promoter activity of the miR-17-92 cluster host gene (MIR17HG) and combined ectopic expression of LEF1 and β-catenin further enhanced the promoter activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…The β‐catenin and LEF1 have been confirmed to function as key downstream effectors in the Wnt signalling pathway . To explore the molecular mechanism of LEF1‐AS1 in retinoblastoma, we conducted western blots to determine the effect of LEF1‐AS1 on β‐catenin and LEF1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The β‐catenin and LEF1 have been confirmed to function as key downstream effectors in the Wnt signalling pathway . To explore the molecular mechanism of LEF1‐AS1 in retinoblastoma, we conducted western blots to determine the effect of LEF1‐AS1 on β‐catenin and LEF1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, we explored the molecular mechanism of LEF1‐AS1 in retinoblastoma. LEF1‐AS1 has been suggested to interact with LEF1 to regulate tumour cell proliferation and mobility, and LEF1 is a key regulatory factor of the Wnt signalling pathway . Therefore, we estimated the effect of LEF1‐AS1 on β‐catenin and LEF1 expression and found that silencing LEF1‐AS1 expression dramatically impaired β‐catenin and LEF1 expression in retinoblastoma cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hotairm1 was found to be downregulated in hepatocellular carcinoma and inhibited the proliferation and promote the apoptosis by suppressing the Wnt/-catenin signaling pathway and then inhibit the tumor progression. (Mu et al, 2019;Zhang et al, 2018) Yuan et al found that the overexpression of interferon regulatory factor-1 (IRF-1) downregulated Mir17hg in gastric cancer cells and inhibited the tumor progression by inhibiting Wnt/-catenin signaling pathway. Yuan et al (2019) Wincr1 was found to be activated by Wnt/-catenin signaling pathway in fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%